KONSEP DIRI MAHASISWA KRISTEN DI UNIVERSITAS MUHAMMADIYAH MALUKU UTARA - Juniarti, Wiwin; Bailussy, Wahyuni (Aksara Public, 2018)
Research entitled "The Concept of Christian Students at Muhammadiyah University of North Maluku". becomes an interesting sight if the campus becomes an option for Christian students. The purpose of this study is To find out how Christian students to form their own concept at the University of Muhammadiyah North Maluku. The type of research used in this study is the type of descriptive qualitative research that aims to describe precisely the properties of an individual, circumstances, symptoms or specific groups to be studied, in this case is the self-concept of Christian students at the University of Muhammadiyah North Maluku. The theory used in this research is self concept. The results show that, Christian students while in the middle of the majority environment of Islamic students form their own concept with their respective judgments and in accordance with the environment in which they are located. They have a positive self-concept. They are not choosing friends, they are friends with everyone without discriminating their religion, ethnicity, culture, physical and status. Initially they were not too close to feel awkward and afraid if not accepted by Islamic students. However, over time they feel happy and familiar with Islamic students.